2018
DOI: 10.5812/ijp.11567
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressive Therapy in Children With Steroid-Resistant Nephrotic Syndrome

Abstract: Background: Treatment of steroid-resistant nephrotic syndrome (SRNS) remains a huge challenge in pediatric patients. Immunosuppressive agents including cyclosporine A (CsA), tacrolimus (TAC) and mycophenolate mofetil (MMF) are recommended for the management of children with SRNS. The aim of this study was to compare the efficacy of CsA, TAC and MMF in children with SRNS and provide guidance for clinical practice. Methods: This is a retrospective analysis of the records of 70 children with SRNS recruited from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…It was noted that MMF was more effective in FR/SD rather than SRNS (95% vs 66%) but not better than CS. More or less similar results have been reported by others [18, 2527]. However, 50% of children required addition of MMF but there was no difference in response (91% vs 87%).…”
Section: Discussionsupporting
confidence: 88%
“…It was noted that MMF was more effective in FR/SD rather than SRNS (95% vs 66%) but not better than CS. More or less similar results have been reported by others [18, 2527]. However, 50% of children required addition of MMF but there was no difference in response (91% vs 87%).…”
Section: Discussionsupporting
confidence: 88%
“…In recent years many studies came up confirming our observations. Li J et al concluded that CsA and Tac as initial therapy for SRNS have a better remission and relapse rate [55]. Genetic screening should be done prior to therapy in familial SRNS and ideally in sporadic SRNS also with initial resistance.…”
Section: Letter To Editormentioning
confidence: 99%